CompTIA security+ exam SY0-501 - Dunkerley, Dawn (Mike Meyers' certification passport., 2018)
"Get on the fast track to becoming CompTIA Security+ certified with this affordable, portable study tool. Inside, cybersecurity experts guide you on your career path, providing professional tips and sound advice along the way. With an intensive focus only on what you need to know to pass CompTIA Security+ Exam SY0-501, this certification passport is your ticket to success on exam day. INSIDE: Itineraries -- List of official exam objectives covered; ETAs -- Amount of time needed to complete each lesson; Travel Advisories -- Expert advice on critical topics; Local Lingo -- Concise definitions of key terms and concepts; Travel Assistance -- Recommended resources for more information; Exam Tips -- Common exam pitfalls and solutions; Checkpoints -- End-of-chapter questions, answers, and explanations; Career Flight Path -- Information on the exam and possible next steps."--